RATIONAL USE OF ANTIPLATELETS IN VASCULAR NEUROINTERVENTION PROCEDURES - Gilbert Tangkudung; David Susanto; Ferrdy Pratama Wijaya (Neurologi Manado, 2021)
Vascular neurointervention procedures have a risk of complications, both intraprocedural and post-procedure. The most common complication is thromboembolic. Administration of antiplatelet agents can prevent the risk of these occurrences. Several antiplatelet agents have been studied and tested in neurointerventional vascular procedures. Knowing the right time and doses of antiplatelet can reduce the side effects that can occur during its administration so it can provide a good outcome after the procedures